Steelgrade app: mobile app for steel product quality assessment - Yeoh, Wei Bin (2024)
The leading steel manufacturer companies in Malaysia named CSC Steel Holding Berhad faces challenges in their existing steel product Quality Assessment System in a way that the steel product evaluation process is carried out manually by the domain experts. This manual evaluation process somehow is tedious, time consuming, and experts dependent. Thus, this project aims to revolutionise the manual evaluation process by leveraging the AI-based solution. Development of a mobile-based Quality Assessment System with CNN algorithm is proposed and implemented to tackle the issue. Steel grading processing via the help of trained CNN model to automate the experts evaluation process, and easy-to-interpret dashboard for the data analysis are the two core functionalities in this proposed mobile application. Rapid Application Development (RAD) phased development methodology is adopted to break down the whole complex application into smaller parts for development. Lastly, testing phases are also conducted to ensure the application is error-free, high user satisfaction and great usability. In conclusion, this project has achieved success, fulfilled all the project objectives, and the application is developed successfully.